Species of Eunicidae (Annelida, Errantia, Eunicida) from rhodolith beds off the states of Paraíba and Pernambuco, northeastern Brazilian coast - Bergamo, Gilberto; Carrerette, Orlemir; Zanol, Joana; de Matos Nogueira, João Miguel (Zootaxa, 2018)
Members of one species of Leodice Lamarck, 1818, one species of Lysidice Lamarck, 1818, and another of Palola Gray in Stair, 1847 were found among material from rhodolith beds, collected off the states of Paraíba and Pernambuco, northeastern Brazilian coast. Of those species, one is new to science and the other two are new records for the state of Pernambuco, although their occurrence on neighbouring areas was already known. Leodice calcaricola sp. nov. resembles morphologically L. miurai (Carrera-Parra & Salazar-Vallejo, 1998) as members of both species share similar body size, moniliform prostomial appendages, similar numbers of branchial filaments (1–3 per branchia), and, especially, by having falcigers with bidentate blades on anterior chaetigers, and tridentate on posterior ones. These species differ, however, since specimens of L. calcaricola sp. nov. have distinctly shorter antennae and palps, homodont and heterodont pectinate chaetae, three types of aciculae and two subacicular hooks per midbody parapodium. The other two species which members were found on the rhodolith beds are Lysidice cf. unicornis (Grube, 1840) and Palola brasiliensis Zanol, Paiva & Attolini, 2000. We describe herein new species to science and provide a redescription for L. cf. unicornis because the Brazilian specimens of this species have never been formally described.